Análisis preliminar de la deformación interna en cuarcitas de la Formación Napostá, Grupo Ventana, Sierras Australes de Buenos Aires - Fortunatti, Natalia Beatriz (2001)
The Sierras Australes fold-and-thrust-belt is located southwest of the Buenos Aires province, Argentina. The chain is composed of a precambrian basement overlied by a middle to upper palaeozoic metasedimentary sequence, and surrounded by tertiary and quaternary deposits. A preliminary microestructural analysis was carried on rocks of the Napostá Formation (orthoquartzites, Ventana Group). A systematic sampling on a section located south to the Abra de la Ventana locality, was performed. Samples were collected in several positions within a key bed that shows the typical style of folding in the sierras: extended normal limbs (SW) and refolded short limbs (NE). The main observations are: 1) In function of the sample locations within the folded bed, the rock shows different rheologic behaviour: normal extended limbs are less deformed showing protomylonitic textures with preservation of a great proportion of relictic grains, scarce recrystallized matrix and neoformed sericite; intensely deformed refolded short limbs show mylonitic textures with flattened and strongly recrystallized relict grains, surrounded by a matrix composed of fine recrystallized quartz grains and sericite. Samples cióse to fold hinges, show more intense mylonitization than those of theneighbouring limbs; 2) Evidences of dynamic recrystallization, involving both grain boundary migration and subgrain rotation mechanisms, have been observed. Grain size reduction took place in a transition between régimen 2 and 3, in the temperature range 250° to 300°C. Presence of fluids during mylonitization is documented by textura] evidences of pressure solution and associated mass transfer mechanisms (straight quartz crystal faces parallel to foliation and new-crystallization of sericite-muscovite in folias and pressure shadows).